P–588 Follicle-stimulating hormone receptor genotype and its influence on the results of double ovarian stimulation in IVF cycles. (6th August 2021) - Horta. Foronda, M; Lledó, B; Ortiz, J A; Fuentes, A; Cascales, A; Lozano, F M; Bernabeu, A; Llácer, J; Bernabeu, R
Abstract: Study question: Does the follicle-stimulating hormone receptor (FSHR) genotype influence the results of the ovarian stimulation treatment in the luteal phase? Summary answer: All patients undergoing in-vitro fertilization benefit from luteal phase ovarian stimulation, regardless of their follicle-stimulating hormone receptor genotype. What is known already: Previous studies suggest that FSH receptor polymorphism in position 680 influences the response to ovarian stimulation in the luteal phase. It was observed that patients with SS genotype seems to require a higher dose to obtain an optimal ovarian response. Later, it was reported that, in patients with SS genotype, a better performance seems to be obtained by administering highly purified urinary FSH while, in SN patients, better results were obtained with recombinant FSH. In patients with NN genotype, no differences were found. Our aim was to test whether this concept is applicable to ovarian stimulation in the luteal phase. Study design, size, duration: One hundred and thirty-four patients were included in a retrospective study between July 2017 and September 2020. In these patients, a double stimulation protocol was carried out and the FSH receptor was genotyped either as part of the pre-treatment fertility tests or for the current study. Patients with a double stimulation treatment who could not be genotyped were excluded from the analysis. Participants/materials, setting, methods: To genotype the 680 position of the FSH receptor, a real-time PCR for allelic discrimination was carried out using StepOnePlus™ Real-Time PCR System (Applied Biosystems™. Ref: 4376600). Non-parametic tests were used to study the differences between the groups. They were performed with the software R Statistical Software, version 4.0.3. Main results and the role of chance: The results of ovarian stimulation in the luteal phase were better compared to the conventional follicular phase. Statistically significant differences (p < 0.001) were found in the number of retrieved oocytes (5.06 versus 3.51), retrieved MII (4.13 versus 2.91), fertilized oocytes (3.22 versus 1.81) and blastocysts formed (1.79 versus 0.62). Furthermore, these differences remained regardless of the genotype for the 680 position of the FSH receptor in all groups (p < 0.05). In addition, better results were obtained in the luteal phase in patients who have been stimulated with the type of gonadotropin that already had better performance in the follicular phase for its genotype, that is, highly purified urinary FSH in SS patients and recombinant FSH in SN patients, compared to other types of gonadotropin (p < 0.05). We also observed that stimulation in the luteal phase lasts longer and consume more gonadotropins than in the follicular phase. This is especially notable in the case of patients with SS genotype, who required slightly higher consumption of gonadotropins compared to the other genotypes in the luteal phase, as had previously been observed in the follicular phase for this genotype. Limitations, reasons for caution: The retrospective study design and the sample size could be a limitation. Furthermore, we cannot determine whether the improvement in luteal phase performance is related to differences in the physiological environment between phases of the cycle or is caused by a possible activation of the ovary from the previous stimulation. Wider implications of the findings: All patients undergoing in-vitro fertilization seems to benefit from luteal phase ovarian stimulation, regardless of their genotype for FSHR. In addition, the pharmacogenetic recommendation when choosing the type of FSH for ovarian stimulation should be the same both in the follicular phase and in the luteal phase. Trial registration number: Not applicable